Inadequate consumption of vitamin A-rich foods among preschool children in Wolaita Sodo, Southern Ethiopia - Mekisso, Selamawit Mathewos; Dake, Samson Kastro; Haile, Dibora Teferi; Nane, Debritu (Frontiers in Nutrition, 2024)
BackgroundThe primary cause of vitamin A deficiency in developing countries like Ethiopia is the inadequate consumption of vitamin A-rich foods. Preschool children are particularly vulnerable due to their higher nutritional requirements and increased susceptibility to infections. This study aims to assess the prevalence of inadequate consumption of vitamin A-rich foods and identify the associated factors among preschool children in Wolaita Sodo, Southern Ethiopia.MethodsA community-based cross-sectional study was conducted using multi-stage sampling to select 471 households with preschool children between July 15 and August 15, 2021. Data analysis was performed using SPSS version 25. Binary logistic regression was employed to identify predictors of inadequate consumption of vitamin A-rich foods. Variables with a p-value <0.25 in the bivariate analysis were included in the multivariable logistic regression. The strength of the associations was estimated using adjusted odds ratios with 95% confidence intervals. Statistical significance was determined at a p-value <0.05.ResultThe prevalence of inadequate consumption of Vitamin A-rich foods among pre-school children in this study was 381 (81.1%) with a 95% confidence interval of 77.3 to 84.9%. Predictors for inadequate consumption of Vitamin A rich foods were being a girl [AOR = 0.41, 95% CI: 0.24, 0.69], aged 46–59 months [AOR = 0.46, 95% CI: 0.23, 0.93], rural residence [AOR = 2.36, 95% CI: 1.22, 4.57], family size of five or more [AOR = 2.36, 95% CI: 1.15, 4.86], household income of <2000 Ethiopian Birr [AOR = 3.98, 95% CI: 1.18, 13.40], and morbidity in last 2 weeks [AOR = 0.36, 95% CI: 0.17, 0.74].ConclusionThis study showed that the participants’ consumption of vitamin A-rich food was inadequate. Greater emphasis be placed on food-based tactics to increase pre-schoolers’ intake of foods high in vitamin A. Enhancing socioeconomic status is also crucial for increasing the intake of foods high in vitamin A.